The Palgrave Handbook of African Political Economy
XXXII, 1106 p. 26 illus., 16 illus. in color.
Keywords: This handbook constitutes a specialist single compendium that analyses African political economy in its theoretical, historical and policy dimensions. It emphasizes the uniqueness of African political economy within a global capitalist system that is ever changing and complex. Chapters in the book discuss how domestic and international political economic forces have shaped and continue to shape development outcomes on the continent. Contributors also provoke new thinking on theories and policies to better position the continent’s economy to be a critical global force. The uniqueness of the handbook lies in linking theory and praxis with the past, future, and various dimensions of the political economy of Africa. Samuel Ojo Oloruntoba is Associate Professor at the Thabo Mbeki African Leadership Institute, University of South Africa, South Africa, and Visiting Scholar at the Institute of African Studies, Carleton University, Canada. Toyin Falola is Jacob and Frances Sanger Mossiker Chair in Humanities and Distinguished Teaching Professor at the University of Texas at Austin, USA.